Mujeres en la historia del movimiento de teatros independientes de Buenos Aires: aportes para la historia de La Cortina y el Teatro Espondeo - Fukelman, María (El Colegio de México A.C., 2018)
The independent theatrical practice, initiated in Buenos Aires from 1930, brought with it some changes in the traditional theatrical tasks. One of them can be seen in the leadership role, which was gaining more prominence. The objectives of this work are: 1) to address the work of different women who carried out leadership roles in the movement of independent theaters; 2) to rescue them from oblivion; 3) to analyze them comparatively; 4) and to link them with their participation within political parties and women’s movements. In this sense, we come to the conclusion that there is a correlation between their involvement in the feminist struggle and the possibility they had (and gave other women) to occupy management positions.